PERAN COMMUNITY ADVICE SEBAGAI PEMODERASI DALAM KEPUTUSAN PEMBELIAN - Pristiana Widyastuti; Alwani Alwani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the influence of rational motives and emotional motives on purchasing decisions with community advice as a moderating variable. This study was conducted on biker as community adviser in Jakarta. The number of samples is 75 data, obtained from the questionaire filled by the respondents. Data analysis uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) test equipment. The results of statistical tests revealed that the rational motives and emotional motives have positive effect on purchasing decisions, whereas community advice has no positive effect on purchasing decisions, it is not able to moderate the relationship among variables. Producer and distributors are important to maintain the quality and reliability of products that rationally influence consumers to buy. In addition, efforts to maintain the credibility of the brand are also important to emphasize the consumer’s pride.